Measuring mental health action competencies in school teachers: internal and external validity evidence - Kerry, Matthew J.; Robin, Dominik; Albermann, Kurt; Dratva, Julia (Frontiers in Digital Health, 2024)
Introduction Mental health literacy is receiving increasing research attention due to growing concerns for mental health globally. Among children, teachers have recently been recognized as playing a vital role in the recognition and reporting of potential mental health issues. Methods A nationally sampled cross-section of teachers was surveyed to examine the discriminant validity of the mental health literacy measure across levels of teaching. A survey collected a total of n = 369 teacher responses in Switzerland (Kindergarten = 76, Primary = 210, Secondary = 83). Item response theory (IRT) analyses were conducted. Results Inspection of psychometric properties indicated removal of two weak performing items. The 15-item measure exhibited a significant mean difference, such that class-responsibility function scored higher (M = 2.86, SD = .45) than non-responsible function (M = 2.68, SD = .45) teachers [t(309) = −2.20, p = .01]. It also exhibited a significant mean difference, such that more subjective experienced scored higher (M = 2.86, SD = .45) than less subjective experienced (M = 2.68, SD = .45) teachers [t(210) = −8.66, p < .01]. Discussion Hypotheses regarding age and role tenure were in the expected direction, but non-significant. The MHL measure for teachers demonstrated sound measurement properties supporting usage across teaching levels.